Bronchial stenosis secondary to epidermolysis bullosa successfully treated with bronchoscopic balloon dilatation. Issue 1 (16th February 2015) - Arya, Rohan; Boujaoude, Ziad; Gratz, Irwin; Akers, Stephen; Abouzgheib, Wissam
Abstract Epidermolysis bullosa rarely affects lower airways. We present a case of lower airway involvement and stenosis successfully managed with flexible bronchoscopy and balloon dilation.